การศึกษาสมรรถภาพเชิงวิชาชีพของนิสิตหลักสูตรการศึกษาบัณฑิต (กศ.บ. 5ปี) มหาวิทยาลัยศรีนครินทรวิโรฒ - สุชาดา สุธรรมรักษ์ และอรรณพ โพธิสุ, ทิพวรรณ เดชสงค์ (Journal of Multidisciplinary in Social Sciences, 2013)
บทคัดย่อ การวิจัยครั้งนี้มีความมุ่งหมายเพื่อ 1) ศึกษาสมรถภาพเชิงวิชาชีพของนิสิตหลักสูตรการศึกษาบัณฑิต (กศ.บ. 5ปี) โดยรวมและรายด้านใน 6 ด้าน คือ ด้านมโนทัศน์ ด้านเทคนิค ด้านบริบท ด้านการติดต่อสื่อสาร ด้านกาบูรณาการ และด้านการปรับตัว และ 2) เปรียบเทียบสมรรถภาพเชิงวิชาชีพของนิสิตหลักสูตรการศึกษาบัณฑิต โดยรวมและรายด้าน จำแนกตาม เพศ คณะวิชา ผลสัมฤทธิ์ทางการเรียนแรงจูงใจใฝ่สัมฤทธิ์ในการเรียน และทัศนคติต่อวิชาชีพครู กลุ่มตัวอย่างประกอบด้วย นิสิตหลักสูตรการศึกษาบัณฑิต (กศ.บ. 5 ปี) ชั้นปีที่ 5 มหาวิทยาลัยศรีนครินทรวิโรฒ โดยใช้ประชากรทั้งหมด เป็นกลุ่มตัวอย่าง รวมจำนวนทั้งสิ้น 221 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล เป็นแบบสอบถามแบบมาตราส่วนประมาณค่า 5 ระดับ จำนวน 62 ข้อ มีค่าความเชื่อมั่นของแบบสอบถามทั้งฉบับเท่ากับ 0.97 สถิตที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย ค่าความเบี่ยงเบนมาตรฐาน การทดสอบที่การวิเคราะห์ความแปรแรวนแบบทางเดียว และการทดสอบเป็นรายคู่ของ เชฟเฟ่ ผลการวิจัยพบว่า 1) นิสิตมีสมรรถภาพเชิงวิชาชีพโดยรวมและเป็นรายด้านอยู่ในระดับมากทุกด้าน 2) นิสิตขายและนิสิตหญิงมีสมรรถภพเชิงวิชาชีพ แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 4) นิสิตที่มีผลสัมฤทธิ์ทางการเรียนต่างกันมีสมรรถภาพเชิงวิชาชีพ โดยรวมไม่แตกต่างกัน Abstract The purposes of this research were 1) to study professional competency of the undergraduate students (5-year curriculum) of Srinakarinwirot University in general and in each of six aspects including conception, technique, context, communication, integration, and adaptation and 2) to compare professional competency in general and in each of six aspects based on gender, faculty, academic achievement, learning motivation and opinion towards teaching profession. The population in this research consisted of 221 fifth-year undergraduate students who studied for a Bachelor of Education at Srinakharinwirot University. The instrument used for collecting data was a five-point Likert rating scale questionnaire. The questionnaire consisted of 62 items with an alpha reliability co-efficient of .97. The data was analyzed by descriptive statistics (frequency, percentage, arithmetic mean, and standard deviation), t-test, one-way ANOVA and Scheffeûs test. The results were as follows: 1) the studentsû professional competency in general and in each aspect was at a high level; 2) male and female students showed insignificant differences in professional competency both in general and in each aspect; 3) the students in different faculties showed insignificant differences in their professional competency in general but showed significant differences (p=.05) when each aspect was compared; 4) the students who differed in academic achievement showed insignificant differences in professional competency in general, but showed significant differences (p=.05) when each aspect was compared; 5) the students who differed in learning motivation showed significant differences (p=.05) in professional competency both in general and in each aspect; 6) the students who differed in opinion towards teaching profession showed significant differences (p=.05) in professional competency both in general and in each aspect. Keywords: Professional competency